Evaluación de factibilidad de la implementación de la inyección de nanopartículas de sílice como método de recobro mejorado para crudos medianos del campo Yarigui-Cantagallo mediante simulación numérica (2017)
There are primary, secondary and improved recovery methods that are developed according to the Field's needs, however, the primary recovery does not influence the increase of reservoir´s energy as the secondary and improved recovery does. Mature fields require such an increase in energy due to their production time, so water, gas or chemical injection methods also known as enhanced recovery methods (EOR) are required to satisfy the hydrocarbon demand of the moment.